Determination of Ranges of Unstable Operation of Axial Compressor for Aircraft Turbine Engines - Adam KOZAKIEWICZ; Maciej ADAMCZYK; Maciej MAJCHER (Problemy Mechatroniki)
Currently, strict requirements are set for aircraft turbine engine performance, which requires introducing larger, more complex, and more loaded compressors. In sub-assemblies designed in this manner, a vital challenge is to maintain stable compressor operation across wide range of operating conditions. This article presents the results of analysis and estimation of the range of unstable operation of an example axial compressor for a turbofan jet engine with high mass flow ratio. The analyses and numerical simulations performed made it possible to estimate the limit performance for compressor operation for two particularly important phases of flight.